Efficacy and safety of Epimedium total flavonoids for primary osteoporosis: a systematic review and meta-analysis - Li, Jinkun; Huang, Xudong; Yuan, Yifeng; Zhang, Haixin; Zhou, Hang; Xiong, Wei; Li, Yuyi; Zhang, Zechen; Qie, Fengqing; Mao, Yingdelong; Liang, Bocheng; Shi, Xiaolin; et al. (Frontiers in Pharmacology, 2024)
Background: Epimedium total flavonoids (EF) have been recommended to be one of the effective components in Traditional Chinese Medicine (TCM) for the treatment of primary osteoporosis (POP) in China. Due to the lack of evidence-based medical evidence on the efficacy and safety of EF for the treatment of POP, the current systematic review and meta-analysis was carried out aimed at evaluating the curative effects and safety profile of EF treatment for POP in order to provide decision making references for clinical research.The PubMed, Cochrane Library, EMBASE, Web of Science, CNKI, Wanfang, and VIP databases were searched from the date of inception to August 11, 2024. The outcomes of effectiveness and safety of included studies were collected to conduct meta-analysis or systematic review.Results: A total of 6 RCTs were included in this study, involving 838 participants. Overall, our results revealed that the experimental group (EG) had comparable results of efficacy to the control group (CG). The lumbar vertebra bone mineral density (BMD) was statistically different compared to the CG (MD = 0.03; 95%CI: 0.01, 0.04; P = 0.0003), but the clinical significance deserved consideration because the 95%CI nearly crossed the invalid line. The femoral neck BMD was neither statistically different nor clinically different between two groups (MD = 0.00; 95%CI: -0.01, 0.02; P = 0.67). The total complication rates were comparable among the two groups (RR = 0.68; 95%CI: 0.39, 1,19; P = 0.18). The quality of the evidence of the present study was judged as moderate and low based on the GRADE analysis.Conclusions: EF treatment exhibited good curative effects and safety. The result was comparable to the CG, including other Chinese patent medicines and calcium and vitamin D supplements. The EF treatment was proved to be a reliable alternative option for POP.